AN EFFECT OF ANCESTORS ON OATS YIELD DURING IRRIGATION OF DRY STEPPE AREA OF BURYATIA - S. N. Shapsovich (Зерновое хозяйство России)
Due to necessity to increase productivity of forage oats in dry steppe area of Buryatia we studied an effect of fodder crops and mixture grasses on oats yield during irrigation. Sunflower and oat-pea mixture gave the greatest amount of plant residues (6,75 t/ha and 6,95 t/ha respectively).  The largest content of nitrate nitrogen (13,34-14,0 mg/kg) was noted after mixtures of grasses with peas, but only 3,14-3,46 mg/kg of it after silage crops and the mixture of two grasses. The least content of it (3,06 mg/kg) was noted after a triple mixture of oats, barley and sunflower.  The productivity of absolutely dry matter of oats after maize and sunflower was 3,34 t/ha and 3,36 t/ha; after a mixture of two grasses it was 3,02 t/ha -3,30 t/ha and after a mixture of oats, barley and sunflower it was 3,34 t/ha. The largest productivity (3,54-3,62 t/ha) was noted after a mixture of oats and barley with peas. The maths analysis showed that double correlation between a content of nitrate nitrogen and grain productivity was direct average – r = 0,395 + 0,102, Q = 0,003. The total water consumption of oats differed slightly (3765-3845 m3/ha).  The co-efficient of determination is R2 = 2,5%. The co-efficient of water consumption is lower after an oat-pea mixture (502 m3/ha), a barley-pea mixture (505 m3/ha) and a mixture of oats, barley and peas (515 m3/ha). The best oats ancestors are considered double and triple mixtures of peas with oats and barley, as they give the greatest amount of plant residues in soil, the worst ancestor is a mixture of oats with spring rye.